SCREENING PRESENCE AND COMPARATIVE EVALUATION OF SIZE NEURORETINOPROTECTIVE EFFECT AMONG SOME DRUGS WITH ANTIOXIDANT ACTION OR MODULATING ACTIVITY ON FORMATION OF GLUTAMATE EXCITOTOXICITY - Комнацька, К.М.; Черешнюк, І.Л.; Ходаківський, О.А.; Прокопенко, С.В. (World of Medicine and Biology, 2016)
The article presents the results of screening studies the presence of neuroretinoprotection effect in Melatonin, Ademol, Citicoline, Mexidol, Corvitin and Thiotriazolin using immunoassay method for assessing activity in serum marker of neuronal destruction – neuron-specific enolase. It was established that all studied organoprotectors had native neucytoprotective activity in terms of the model of eye contusion caused by the action of carbon dioxide under pressure that is developed in the reliably de-escalation of activity investigated marker. The greatest protective effect was found in Melatonin and Ademol. Their therapeutic use in the proposed doses helps to preserve the integrity of retinal neurons in this condition. The data is the basis for the implementation of these drugs in ophthalmic practice for the practical treatment of traumatic lesions of the visual analyzer different genesis.